The association between the gut microbiota metabolite trimethylamine N-oxide and heart failure - Jarmukhanov, Zharkyn; Mukhanbetzhanov, Nurislam; Kozhakhmetov, Samat; Nurgaziyev, Madiyar; Sailybayeva, Aliya; Bekbossynova, Makhabbat; Kushugulova, Almagul (Frontiers in Microbiology, 2024)
This systematic review explores the relationship between the gut microbiota metabolite trimethylamine N-oxide (TMAO) and heart failure (HF), given the significant impact of TMAO on cardiovascular health. A systematic search and meta-analysis of peer-reviewed studies published from 2013 to 2024 were conducted, focusing on adult patients with heart failure and healthy controls. The review found that elevated levels of TMAO are associated with atherosclerosis, endothelial dysfunction, and increased cardiovascular disease risk, all of which can exacerbate heart failure. The analysis also highlights that high TMAO levels are linked to reduced left ventricular ejection fraction (LVEF) and glomerular filtration rate (GFR), further supporting TMAO’s role as a biomarker in heart failure assessment. The findings suggest that interventions targeting gut microbiota to reduce TMAO could potentially benefit patients with heart failure, although further research is needed to evaluate the effectiveness of such approaches.